2023
DOI: 10.3390/molecules28062624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Treatment of Psilocybin and Eugenol on Lipopolysaccharide-Induced Brain Inflammation in Mice

Abstract: Inflammation is an organism’s biological defense mechanism. Acute and chronic inflammation of the body triggers the production of pro- and anti-inflammatory pathways that can affect the content of cytokines in the brain and thus cause brain inflammation. Disorders such as depression and posttraumatic stress disorder (PTSD) are often associated with elevated inflammation. Recently, positive and promising clinical results of psilocybin for the treatment of depression and PTSD were reported. Thus, we decided to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 57 publications
2
7
1
Order By: Relevance
“… 46 In combination with psilocybin, it was able to protect against inflammation induced in mice brain by LPS where several cytokines levels such as TNF, IL-1β, IL-6 were reduced. 47 This was also reproducible in other experimental model based on aluminum chloride induced neurotoxicity. 48…”
Section: Resultssupporting
confidence: 71%
“… 46 In combination with psilocybin, it was able to protect against inflammation induced in mice brain by LPS where several cytokines levels such as TNF, IL-1β, IL-6 were reduced. 47 This was also reproducible in other experimental model based on aluminum chloride induced neurotoxicity. 48…”
Section: Resultssupporting
confidence: 71%
“…Next, we tested the efficacy of psilocybin and eugenol to prevent the inflammatory response induced by TNF-α/IFN-γ. While our previous studies have demonstrated psilocybin and eugenol have synergistic effects on COX-2 and IL-6 within HSIEC in vitro [12], as well as synergistic effects on reducing COX-2 and IL-6 levels within the LPS-induced murine brain inflammation [22], in this study, we only saw synergistic effects at the highest dose of psilocybin (40 µM) combined with eugenol (25 µM) (Table 1). With the combined treatment of psilocybin (40 µM) and eugenol (25 µM), there was a fold change of −21.0× and −62.5× for TNF-α and IFN-γ, respectively, which was superior to both psilocybin's induced fold changes of −13.7× and −9.5×, or eugenol's induced fold changes of −8.8× and −17.0× for TNF-α and IFN-γ, respectively (Table 1).…”
Section: Discussioncontrasting
confidence: 65%
“…Previously, we have shown eugenol has potent anti-inflammatory effects and shows synergy with psilocybin in vivo within the brain [22], as well as in vitro within small intestinal epithelial cells [12]; however, outside of cell models, the effects of eugenol on IBD still remains unknown. Although eugenol is still being studied, it is demonstrating potential as an IBD therapeutic and has been declared by World Health Organization (WHO) to be generally recognized as safe and non-mutagenic [23].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that psilocybin reduced inflammation in the brains of rats by decreasing the activity of certain immune cells called microglia [ 8 ]. Recently, the oral administration of psilocybin and eugenol in vivo ameliorated LPS-induced inflammation within the brain [ 9 ]. While more research is needed to fully understand the anti-inflammatory effects of psilocybin, these findings suggest that it may have potential as a therapeutic agent for a range of conditions characterized by inflammation in the body or brain.…”
Section: Introductionmentioning
confidence: 99%